Mitochondrial DNA of Yoshida ascites tumour cells. Physicochemical properties and biological function (Revista Española de Fisiología, 1976)
Mitochondrial DNA from Yoshida A.H. 130 cells, has been characterized by determination of the buoyant density by CsCl equilibrium density gradient centrifugation and the thermal denaturation and renaturation behaviour. These studies have been carried out parallelly on nuclear DNA from the same cells in order to search for possible differences between both DNAs. Mitochondrial DNA of Yoshida cells presents an equilbrium in CsCl of 1.7154 g/cm3 and a sharp melting with a Tm of 92 degrees C. Nuclear DNA presents an equilibrium of 1.7030 g/cm3 and a Tm of 88 degrees C. The guanine plus cytosine content in both DNAs has been calculated from tumour results and compared with the content in normal rat liver cells M-DNA of tumour cells presents a higher guanine plus cytosine content than N-DNA, whereas in normal liver cells is higher in N-DNA. N-DNAs of both normal and tumour cells have the same guanine plus cytosine content, whereas M-DNA from tumour cells presents a significant increase (about 35%) with regard to this from normal liver cells.